ҚАҲАРМАН ПСИХОЛОГИЯСЫ ҲӘМ ШЕБЕРЛИК (Т.Қайыпбергеновтың «Тәнҳә өзиңе мәлим сыр» повести мысалында) - Сәрсенбаев, Қ.Ж. (SCIENCE and SOCIETY, 2022)
The article examines the ability of the Karakalpak people’s writer T.Kaiypbergenov to create the psychology of a hero. The examples given in the article are collected from the writer’s story «Тәнҳә өзиңе мәлим сыр».